A study on influencing factors of optimum insulation thickness of exterior walls for rural traditional dwellings in northeast of Sichuan hills, China. (June 2022) - Hou, Jiawen; Zhang, Tao; Liu, Zu'an; Hou, Chaoping; Fukuda, Hiroatsu
Abstract: Thermal performance of exterior walls can be improved with increasing insulation thickness, but the corresponding material cost will also rise. Therefore, the optimum thickness of insulation material necessarily exists when the economy is considered. Adding insulation materials with the optimum thickness for exterior walls of rural traditional dwellings in northeast of Sichuan hills can effectively enhance their thermal performance and lighten the economic burden of residents while decreasing energy consumption. Hence, the optimum thickness of five insulation materials was calculated by using the degree-days method and P 1 -P 2 economic model as well as the energy-saving and economic benefits were evaluated based on EnergyPlus and dynamic investment payback period model. Then the influence law and the impact degree of influencing factors on the optimum thickness were analyzed via orthogonal test and analysis of variance. Eventually, the remarkable energy-saving and economic benefits of modifying the most crucial factor (heating-degree day) were assessed. Results show that the optimum insulation thickness ranges from 0.081 m to 0.144 m under the local climate and economic context. Besides, rationally lowering the heating-degree day can increase the energy-saving rate and economic benefits by 29.5% and 78.2%, respectively. The results can provide some new insights into the energy-saving retrofit of local traditional dwellings. Highlights: Reveal optimum economic insulation thickness for local dwellings exterior walls. Evaluate energy-saving and economic benefits of insulation with optimum thickness. Quantify the impact degree of impact factors on optimum thickness and rank them. Heating degree-day has the highest significance on optimum thickness by ANOVA. Assess energy-saving and economic potential after lowering heating degree-day.